The concept of Kidya in the Abbasid era (132-656AH / 750-1258AD) - AbdulMonam, Enas Imad (Al-Adab Journal, 2022)
The phenomenon of kidiyah emerged in the era of the Umayyads, but it became stronger and intensified in the Abbasid eras, with the development, complexity and intertwining of social life in various aspects, and the replacement of money with the supreme place in human values, The class disparity was the main reason behind the people’s scramble to collect money by various means, and they did not shy away from the evil or the forbidden, so there were many ways of deception and fraud to reach the money that contributed to the emergence of the literature of the kidya, as the destitute groups sought for their food, and collected money by every means, so begging was one of the these means.This research aims to study the phenomenon of kidya, which in the sense of asking and asking for giving, is a natural phenomenon in all societies.